Estratégias metacognitivas no ensino de física : análise de uma intervenção didática no ensino médio - Biazus, Marivane de Oliveira (2021)
The research starts with the recognition that some students who attend High School show difficulties in Physics comprehension, which can be eased through the activation of metacognitive thinking during the learning activities. Studies in the area of Physics that point to the use of metacognitive thinking as one of the factors that differentiate the students who show ease from those who have more difficulties in this subject bring up this premise. In theory, the present investigation is guided by the understanding of metacognition, of its components and elements by Rosa (2011) e through the discussions of Monereo and collaborators (1994; 2001) about the use of metacognitive strategies in the scholar context. Viewing that, the research aims to evaluate the contributions of a didactic intervention process oriented by metacognitive strategies to mobilize the metacognitive thinking of the students, in a way to make them more conscious of their knowledge and capable of proceeding action of self-regulation in learning situations. As research quotation is the following: which effects are noticed in the and by the students, in terms of metacognitive thinking, before a process of didactic intervention in Physics guided by metacognitive strategies? Considering the fact that the students with difficulties in learning mention not invoking the metacognitive thinking during the activities, a reorganization of actions of the Physics curricular component is proposed, so they start involving metacognitive strategies. The implementation of the proposal, which is organized in six meetings, promoted in alternative terms to the regular lessons, is restricted to a small group of students who claim to have learning difficulties. Methodologically, the study is anchored in the qualitative perspective, involving pre and post-test questionnaires, such as the collection of written and oral registration made by the students during the didactic intervention and at the end of each meeting by the researcher, who is the group’s teacher. The results point out to the viability of the proposal, since they identify that the students proceed to the mobilization of their thoughts by means of didactic actions adopted during the meetings. However, this occurs in a distinct way to each member of the research and to each metacognitive element in analysis.